What do users think of the UK's three COVID-19 contact-tracing apps? A comparative analysis. Issue 1 (19th July 2021) - Garousi, Vahid; Cutting, David
Abstract : Objectives: Our goal was to gain insights into the user reviews of the three COVID-19 contact-tracing mobile apps, developed for the different regions of the UK: 'NHS COVID-19' for England and Wales, 'StopCOVID NI' for Northern Ireland and 'Protect Scotland' for Scotland. Our two research questions are (1) what are the users' experience and satisfaction levels with the three apps? and (2) what are the main issues (problems) that users have reported about the apps? Methods: We assess the popularity of the apps and end users' perceptions based on user reviews in app stores. We conduct three types of analysis (data mining, sentiment analysis and topic modelling) to derive insights from the combined set of 25 583 user reviews of the aforementioned three apps (submitted by users until the end of 2020). Results: Results show that end users have been generally dissatisfied with the apps under study, except the Scottish app. Some of the major issues that users have reported are high battery drainage and doubts on whether apps are really working. Discussion: Towards the end of 2020, the much-awaited COVID-19 vaccines started to be available, but still, analysing the users' feedback and technical issues of these apps, in retrospective, is valuable to learn the right lessons to be ready for similar circumstances in future. Conclusion: Our results show that more work is needed by the stakeholders behind the apps (eg, apps' software engineering teams, public-health experts and decision makers) to improve the software quality and, as a result, the public adoption of these apps. For example, they should be designed to be as simple as possible to operate (need for usability).